2019
DOI: 10.1177/0272989x19855050
|View full text |Cite
|
Sign up to set email alerts
|

Facts and Fears in Public Reporting: Patients’ Information Needs and Priorities When Selecting a Hospital for Cancer Care

Abstract: Objective. Public reporting on the quality of provider care has the potential to empower patients to make evidence-based decisions. Yet patients seldom consult resources such as provider report cards in part because they perceive the information as irrelevant. To inform more effective public reporting, we investigated patients’ information priorities when selecting a hospital for cancer treatment. We hypothesized that patients would be most interested in data on clinical outcomes. Methods. An experienced moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 85 publications
(74 reference statements)
1
7
0
Order By: Relevance
“…To improve the timeliness of elective surgery for cancer and other conditions, many countries have introduced healthcare reforms involving national targets and performance measures [ 5 ]. Previous studies have shown that patients with cancer support public reporting of care quality, timeliness, and patient satisfaction/experience [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…To improve the timeliness of elective surgery for cancer and other conditions, many countries have introduced healthcare reforms involving national targets and performance measures [ 5 ]. Previous studies have shown that patients with cancer support public reporting of care quality, timeliness, and patient satisfaction/experience [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found that four-year risk-adjusted mortality ratios of cancer patients are reasonably consistent for larger volumes of FFS Medicare patients, but less so for hospitals with lower volumes. Among higher volume hospitals (defined as 335 Medicare patients or more), long-term mortality could be added to the list cancer care quality metrics (8,9). and be a useful metric for patients' when selecting hospital for cancer care.…”
Section: Discussionmentioning
confidence: 99%
“…Proponents of reporting cancer volume argue that at the very least patients deserve to have access to hospital volume information to inform decision-making (24). And while patients are interested in volume, it does not serve as a replacement for surgical outcomes data, but rather can be used as additional information to inform decision-making or quality improvement efforts (7). Information on hospital cancer surgery volume could provide more comprehensive data to guide existing policy-relevant research, including studies on the centralization of surgery, the volume-outcome relationship, and minimum surgical case-load requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Estimating hospitals' all-payer volume of cancer surgeries from Fee-for-Service Medicare claims care (7).…”
Section: Original Articlementioning
confidence: 99%